Enhanced OCA (Optical Clear Adhesive) as well as preparation method and application thereof
By optimizing the formulation and process, combined with multiple reactions and heat treatments of components such as acrylic monomers, an enhanced OCA optical glue is formed, which solves the compatibility, application accuracy and cost-effectiveness of OCA optical glue in high-filled blind holes. High filling performance and durability are achieved.
Patent Information
- Application Number
- CN202411664342.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-01-14
AI Technical Summary
In high-filled blind hole technology, OCA optical glue needs to be compatible with conductive materials and substrate materials, and the application process needs to be precisely controlled to avoid bubbles or uneven filling, and cost-effectiveness is required to accommodate large-scale production.
By optimizing the formulation and process, including a combination of acrylic monomers, crosslinkers, initiators, free radical capture agents and modifiers, mixing with 1-hydroxycyclohexyl ketone, isopropanol and acetonitrile after multiple reactions, coating It is clothed on the film and baked, pressurized and defoamed to form a reinforced OCA optical glue.
It significantly improves the bonding strength and durability of OCA optical adhesives, adapts to the needs of complex structures, and achieves a balance of high filling performance and cost-effectiveness without reducing transparency.
Smart Images

Figure BDA0005144231010000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer material modification and application, and specifically relates to an enhanced OCA optical adhesive and a preparation method and application thereof. Background Art
[0002] As electronic devices develop towards thinness, high resolution and multi-function, display technology has also experienced significant progress. Modern displays, especially flexible displays and foldable displays, require higher integration and more sophisticated circuit design. Among them, high-filled blind hole technology plays an important role in display manufacturing, which allows complex circuit layouts to be realized in the multi-layer structure of the display. This technology enables the display to integrate more functions, such as touch sensing, light-emitting elements, etc., while maintaining its thin and light appearance. High-filled blind hole technology faces various challenges. First, high-filled blind holes need to ensure good electrical connection performance. Any voids or cracks may affect the performance of the display. Secondly, the display generates heat when it is working. The mismatch in the thermal expansion coefficients of the conductive material and the substrate material in the high-filled blind hole may lead to performance degradation. Finally, the display has strict requirements on optical performance, and the presence of high-filled blind holes should not affect the display effect.
[0003] As an optically transparent adhesive, OCA optical adhesive has been widely used in the bonding between the touch layer and the display layer of the display screen. In the application of high-filled blind holes, OCA optical adhesive can provide additional advantages. First, the high transparency of OCA optical adhesive ensures that the display effect of the display screen is not affected; second, the high bonding strength of OCA optical adhesive can enhance the bonding between the high-filled blind hole and the substrate, and improve the stability of the overall structure; finally, OCA optical adhesive can serve as a protective layer to prevent the high-filled blind hole from being damaged during the subsequent manufacturing process, playing a protective role.
[0004] Although OCA optical adhesive has potential application value in display manufacturing, it still faces challenges in the application of high-filled blind holes. First, OCA optical adhesive needs to be compatible with the conductive material and substrate material in the high-filled blind holes to ensure electrical performance and bonding strength; second, the application of OCA optical adhesive needs to be precisely controlled to avoid bubbles or uneven filling in the high-filled blind holes, which has high requirements for the manufacturing process; third, while maintaining performance, the application of OCA optical adhesive also needs to consider cost-effectiveness to meet the needs of large-scale production. Summary of the invention
[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0006] The purpose of the present invention is to provide a method for preparing an enhanced OCA optical glue and film, which improves the bonding performance, durability and ability to adapt to complex structures of the products by optimizing the formula and process.
[0007] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0008] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing an enhanced OCA optical adhesive.
[0009] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising:
[0010] The acrylic monomer and the cross-linking agent are dissolved in a solvent, and after stirring and deoxygenation, an initiator is added to carry out a primary reaction, a free radical scavenger is added to carry out a secondary reaction, and a modifier is added to carry out a tertiary reaction to obtain a polymer;
[0011] The polymer, 1-hydroxycyclohexyl phenyl ketone, cross-linking agent, isopropyl alcohol and / or acetonitrile are mixed in a mass ratio of 70-80:0.2-1:0.3-5:20-30 under vacuum, coated on a heavy release film, baked, pressurized to remove bubbles, and then covered with a light release film to obtain an enhanced OCA optical adhesive;
[0012] The mass ratio of the acrylic acid monomer, crosslinking agent, initiator, free radical scavenger and modifier is 90-110: 0.4-0.6: 0.2-0.5: 0.4-0.6: 0.1-0.2; in the polymer reaction system, the mass ratio of the acrylic acid monomer and the crosslinking agent to the solvent is 50-60%.
[0013] As a preferred embodiment of the method for preparing the enhanced OCA optical adhesive described in the present invention, the acrylic monomer includes one or more of isooctyl acrylate, hydroxybutyl acrylate, acryloylmorpholine, acrylamide, isooctadecanyl acrylate, and isododecyl acrylate.
[0014] As a preferred scheme for the preparation method of the enhanced OCA optical adhesive described in the present invention, the cross-linking agent is a multifunctional acrylate, including one or more of trimethylolpropane tri(meth)acrylate, tripentaerythritol octaacrylate, ethoxylated trimethylolpropane triacrylate, pentaerythritol tetraacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate, and trimethylolpropane tris(3-mercaptopropionic acid) ester; and the solvent includes tetrahydrofuran.
[0015] As a preferred scheme for the preparation method of the enhanced OCA optical adhesive described in the present invention, the initiator includes one or more of hydrogen peroxide, dimethyl azobisisobutyrate, azobisisobutyronitrile, azobisisovaleronitrile, azobiscyclohexylcarbonitrile, 2,2'-azobis(N-butyl 2-methylpropionamide), 1,2-bis(2,4,4-trimethyl-2-pentyl)diazepine, and 2,2'-azo-bis-(2,4-dimethyl-4-methoxyvaleronitrile).
[0016] As a preferred scheme for the preparation method of the enhanced OCA optical adhesive described in the present invention, the free radical scavenger includes one or more of 2,2,6,6-tetramethyl-1-(undecanyloxy)-4-piperidinol carbonate, 1,2,3,4-butanetetracarboxylic acid and 2,2-bis(hydroxymethyl)-1,3-propanediol and 3-hydroxy-2,2-dimethylpropanal, 1,2,2,6,6-pentamethyl-4-piperidinyl ester polymer, tetramethylpiperidinoxide, phenothiazine, and 2,6-di-tert-butyl-4-methylphenol.
[0017] As a preferred embodiment of the method for preparing the enhanced OCA optical adhesive of the present invention, the method for preparing the modifier comprises:
[0018] The modifier monomers A and B are mixed in a mass ratio of 0.5 to 2:1 and added into tetrahydrofuran, stirred to remove oxygen, and reacted at 50 to 70° C. for 5 to 10 hours to obtain a modifier;
[0019] Wherein, the modifier monomer A includes one or more of hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxybutyl (meth)acrylate; the modifier monomer B includes one or more of N-hydroxymethyl acrylamide, isophorone diisocyanate, or hydrogenated dicyclohexylmethane diisocyanate.
[0020] As a preferred embodiment of the method for preparing the enhanced OCA optical adhesive described in the present invention, the reaction temperature is 50 to 80° C. and the reaction time is 4 to 24 hours.
[0021] As a preferred embodiment of the method for preparing the enhanced OCA optical adhesive described in the present invention, the baking comprises the following steps: the baking temperature is 60 to 100° C., the baking time is 3 to 10 minutes, and the heating rate is 3 to 8° C. / min.
[0022] Another object of the present invention is to overcome the deficiencies in the prior art and provide an enhanced OCA optical adhesive.
[0023] The third object of the present invention is to overcome the deficiencies in the prior art and provide an application of an enhanced OCA optical adhesive in display screen manufacturing.
[0024] Beneficial effects of the present invention:
[0025] (1) The OCA optical adhesive formula prepared by the present invention includes a polymer component, a crosslinking agent component, a solvent component, an initiator component, a free radical scavenger component, a modifier component and other auxiliary components, and has excellent filling performance. It can significantly improve the bonding strength of the product without reducing the transparency of the product.
[0026] (2) The present invention has great practical applicability and is cost-effective and adaptable to large-scale production needs. DETAILED DESCRIPTION
[0027] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0028] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0029] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor is it a separate or selective embodiment that is mutually exclusive with other embodiments.
[0030] The raw materials used in the present invention are all commercially available unless otherwise specified.
[0031] Dimethyl azobisisobutyrate was entrusted to Jiangsu Lianying New Materials Co., Ltd. for purification.
[0032] The performance of the material prepared in the embodiment of the present invention was tested as follows:
[0033] A polarizer with a thickness of 72 μm and a single hole of 4 mm was selected and attached to the optical glass, and then pressurized to remove bubbles and cooled to room temperature;
[0034] The prepared OCA optical adhesive was attached to the optical glass and then vacuum-bonded with the above-mentioned polarizer and pressurized to remove bubbles. After cooling to room temperature, it was placed under three conditions: 85°C for 500 hours, 85°C with 85% humidity, and -40 to 85°C / 150 cycles, and irradiated with UV at an irradiance of 290 to 400nm for aging tests to verify the filling performance of the OCA optical adhesive.
[0035] Example 1
[0036] This embodiment provides a method for preparing an enhanced OCA optical adhesive, specifically:
[0037] (1) 0.5 equivalent of hydroxyethyl (meth)acrylate and 1.0 equivalent of isophorone diisocyanate were added into a reaction kettle at a solid content of 50%, and tetrahydrofuran was added, and stirred to remove oxygen; the reaction was carried out at 60° C. for 8 hours to obtain a modifier.
[0038] (2) With a solid content of 45%, 60 g of isooctyl acrylate, 5 g of hydroxybutyl acrylate, 5 g of acryloylmorpholine, 5 g of acrylamide, 25 g of isooctyl acrylate, and 0.5 g of trimethylolpropane tris(3-mercaptopropionate) are weighed in sequence, dissolved in tetrahydrofuran, and stirred to remove oxygen; then 0.3 g of dimethyl azobisisobutyrate is added, and the reaction is carried out at 60° C. for 24 h; 0.5 g of 2,2,6,6-tetramethyl-1-(undecanyloxy)-4-piperidinol carbonate is added, and the reaction time is 4 h; 0.1 g of a modifier is added, and the reaction time is 4 h; and a polymer is obtained.
[0039] (3) The polymer, 1-hydroxycyclohexyl phenyl ketone, cross-linking agent and isopropyl alcohol were mixed in a vacuum at a mass ratio of 75:0.6:2.65:25, and then coated on a heavy release film with a thickness of 100 μm. The mixture was then placed in a 50°C oven and heated to 100°C at a rate of 3°C / min, maintained for 5 min, taken out, and covered with a light release film to obtain an OCA optical adhesive.
[0040] Example 2
[0041] The difference between this embodiment and embodiment 1 is that the reaction raw materials of the polymer and the reaction solvent of the OCA optical adhesive are adjusted, and the rest of the preparation process is the same as that of embodiment 1 to prepare the OCA optical adhesive. Specifically:
[0042] (1) Preparation of blocked 2-(2-isocyanatoethoxy)ethyl 2-methylprop-2-enoate: 1.0 equivalent of methyl ethyl ketone oxime and 1.0 equivalent of 2-(2-isocyanatoethoxy)ethyl 2-methylprop-2-enoate were weighed in sequence at a solid content of 50%, toluene was added, the temperature was raised to 65° C., and the reaction was continued for 8 hours to obtain blocked 2-(2-isocyanatoethoxy)ethyl 2-methylprop-2-enoate;
[0043] (2) With a solid content of 45%, 90 g of isooctyl acrylate, 3 g of hydroxybutyl acrylate, 3 g of acrylamide, and 4 g of blocked 2-(2-isocyanatoethoxy)ethyl 2-methylprop-2-enoate are weighed in sequence, dissolved in toluene, and stirred to deoxygenate; then 0.3 g of dimethyl azobisisobutyrate is added, the temperature is raised to 60° C., and the time is set for 24 h; after 24 h, 0.3 g of 2,6-di-tert-butyl-4-methylphenol is added, and the time is set for 4 h; the temperature is raised to 110° C.; 0.5 g of trimethylolpropane tris(3-mercaptopropionate) is added, and the time is set for 4 h; after the time is set, the material is discharged to obtain a polymer.
[0044] (3) The polymer, 1-hydroxycyclohexyl phenyl ketone, cross-linking agent, isopropyl alcohol and acetonitrile were mixed in a vacuum at a mass ratio of 75:0.6:2.65:25, and then coated on a heavy release film with a thickness of 100 μm. The mixture was then placed in a 50°C oven and heated to 100°C at a rate of 3°C / min, maintained for 5 min, taken out, and covered with a light release film to obtain an OCA optical adhesive.
[0045] The performance of the material prepared in the above embodiment was tested, and the comparison results with those in Example 1 are shown in Table 1.
[0046] Table 1
[0047] 85℃500h 85℃ 85% humidity 500h -40~85℃ / 150 cycles Example 1 No bubbles No bubbles No bubbles Example 2 No bubbles No bubbles No bubbles
[0048] It can be seen from the above table that under the experimental conditions of 85°C for 500h, 85°C and 85% humidity for 500h, and -40 to 85°C / 150 cycles, no bubbles appeared in the OCA optical adhesive of the present invention, indicating that the filling performance of the OCA optical adhesive of the present invention is very excellent.
[0049] Example 3
[0050] The difference between this embodiment and embodiment 1 is that the reaction temperature of the polymer is adjusted to 50° C., and the rest of the preparation process is the same as that of embodiment 1 to prepare OCA optical adhesive.
[0051] Example 4
[0052] The difference between this embodiment and embodiment 1 is that the reaction temperature of the polymer is adjusted to 65° C., and the rest of the preparation process is the same as that of embodiment 1 to obtain OCA optical adhesive.
[0053] Example 5
[0054] The difference between this embodiment and embodiment 1 is that the reaction temperature of the polymer is adjusted to 80° C., and the rest of the preparation process is the same as that of embodiment 1 to prepare OCA optical adhesive.
[0055] The performance of the material prepared in the above embodiment was tested, and the comparison results with those in Example 1 are shown in Table 2.
[0056] Table 2
[0057]
[0058] It can be seen from the above table that adjusting the polymer reaction temperature has a significant effect on the performance of OCA optical adhesive. This is because the curing of OCA adhesive can be achieved by thermal curing or ultraviolet curing. Reaction temperature is a key factor affecting the curing speed. Within a certain range, as the temperature increases, the molecular movement accelerates, and the activity of the thermal initiator or photoinitiator increases, thereby promoting the generation of free radicals or ions and accelerating the curing reaction. However, too high a temperature may cause the initiator to decompose too quickly, producing a large number of free radicals, which in turn causes the polymerization reaction to get out of control, and even cause the adhesive layer to turn yellow or the performance to deteriorate. The appropriate temperature can ensure that the adhesive layer is fully cured and form a stable cross-linked network structure, thereby improving the strength and weather resistance of the adhesive layer. Conversely, too low a temperature may result in incomplete curing, affecting the performance and service life of the adhesive layer. In summary, the preferred polymer reaction temperature is 60°C.
[0059] Example 6
[0060] The difference between this embodiment and embodiment 1 is that the modifier monomer A, hydroxyethyl (meth)acrylate, is adjusted to hydroxybutyl (meth)acrylate, and the rest of the preparation process is the same as that of embodiment 1 to prepare OCA optical adhesive.
[0061] Example 7
[0062] The difference between this embodiment and embodiment 1 is that the modifier monomer B isophorone diisocyanate is adjusted to hydrogenated dicyclohexylmethane diisocyanate, and the rest of the preparation process is the same as that of embodiment 1 to prepare OCA optical adhesive.
[0063] The performance of the material prepared in the above embodiment was tested, and the comparison results with those in Example 1 are shown in Table 3.
[0064] Table 3
[0065] 85℃500h 85℃ 85% humidity 500h -40~85℃ / 150 cycles Example 1 No bubbles No bubbles No bubbles Example 6 No bubbles There are bubbles There are bubbles Example 7 There are bubbles There are bubbles There are bubbles
[0066] As can be seen from the table above, adjusting the composition of the modifier monomer has a significant effect on the performance of OCA optical adhesives. This is because the molecular structure has a very obvious effect on Tg. The longer molecular chain of hydroxybutyl acrylate makes it easier for water vapor to enter, thus affecting the bonding performance. Hydrogenated dicyclohexylmethane diisocyanate has a higher Tg, so that the cohesive strength of the system is greater than the bonding strength during curing, resulting in water vapor entering. In summary, the preferred modifier monomers are hydroxyethyl (meth)acrylate and isophorone diisocyanate.
[0067] Example 8
[0068] The difference between this embodiment and embodiment 1 is that dimethyl azobisisobutyrate is replaced by azobisisobutyronitrile, and the rest of the preparation process is the same as that of embodiment 1 to prepare OCA optical adhesive.
[0069] Example 9
[0070] The difference between this embodiment and embodiment 1 is that dimethyl azobisisobutyrate is replaced by azobisisovaleronitrile, and the rest of the preparation process is the same as that of embodiment 1 to prepare OCA optical adhesive.
[0071] The performance of the material prepared in the above embodiment was tested, and the comparison results with those in Example 1 are shown in Table 4.
[0072] Table 4
[0073] 85℃500h 85℃ 85% humidity 500h -40~85℃ / 150 cycles Example 1 No bubbles No bubbles No bubbles Example 10 There are bubbles There are bubbles There are bubbles Embodiment 11 There are bubbles There are bubbles There are bubbles
[0074] As can be seen from the above table, adjusting the initiator has a significant effect on the performance of OCA optical adhesive, which is mainly reflected in the effect of the initiator on the polymerization reaction rate and the molecular structure of the polymer. The initiator plays a key role in the preparation process of OCA optical adhesive. It can absorb ultraviolet light or thermal energy and generate free radicals, thereby initiating the polymerization reaction of the monomer. Different initiators have different spectral absorption characteristics and reactivity, which directly affect the polymerization reaction rate and the molecular weight distribution of the polymer. In summary, the preferred initiator is dimethyl azobisisobutyrate.
[0075] Comparative Example 1
[0076] The difference between this comparative example and Example 1 is that the solvent tetrahydrofuran is adjusted to butyl acetate, and the rest of the preparation process is the same as that of Example 1 to prepare OCA optical adhesive.
[0077] Comparative Example 2
[0078] The difference between this comparative example and Example 1 is that the solvent tetrahydrofuran is adjusted to γ-butyrolactone, and the rest of the preparation process is the same as that of Example 1 to prepare OCA optical adhesive.
[0079] The performance of the material obtained in the above comparative example was tested, and the comparison results with those of Example 1 are shown in Table 5.
[0080] Table 5
[0081] 85℃500h 85℃ 85% humidity 500h -40~85℃ / 150 cycles Example 1 No bubbles No bubbles No bubbles Comparative Example 1 There are bubbles There are bubbles There are bubbles Comparative Example 2 There are bubbles There are bubbles There are bubbles
[0082] As can be seen from the above table, adjusting the type of solvent has a significant effect on the performance of OCA optical adhesive. This is because the increase in molecular weight depends on the chain transfer constant of the solvent. Butyl acetate and γ-butyrolactone cause the molecular structure strength to be too low or too high. The performance of OCA optical adhesive, such as optical clarity, adhesion, weather resistance, etc., are closely related to its molecular structure strength. Too low molecular structure strength may lead to problems such as insufficient adhesion and decreased weather resistance; while too high molecular structure strength may affect optical clarity or cause processing difficulties. In summary, the preferred solvent is tetrahydrofuran.
[0083] In summary, by simulating actual application scenarios and conducting UV aging tests, it is verified that the OCA optical adhesive of the present invention has excellent filling performance. The present invention can provide a method for preparing an enhanced OCA optical adhesive, which improves the product's bonding performance, durability, and ability to adapt to complex structures by optimizing the formula and process.
[0084] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing an enhanced OCA optical adhesive, characterized in that: include, The acrylic monomer and the cross-linking agent are dissolved in a solvent, and after stirring and deoxygenation, an initiator is added to carry out a primary reaction, a free radical scavenger is added to carry out a secondary reaction, and a modifier is added to carry out a tertiary reaction to obtain a polymer; The polymer, 1-hydroxycyclohexyl phenyl ketone, cross-linking agent, isopropyl alcohol and / or acetonitrile are mixed in a mass ratio of 70-80:0.2-1:0.3-5:20-30 under vacuum, coated on a heavy release film, baked, pressurized to remove bubbles, and then covered with a light release film to obtain an enhanced OCA optical adhesive; The mass ratio of the acrylic acid monomer, crosslinking agent, initiator, free radical scavenger and modifier is 90-110: 0.4-0.6: 0.2-0.5: 0.4-0.6: 0.1-0.2; in the polymer reaction system, the mass ratio of the acrylic acid monomer and the crosslinking agent to the solvent is 50-60%.
2. The method for preparing the enhanced OCA optical adhesive according to claim 1, characterized in that: The acrylic monomer includes one or more of isooctyl acrylate, hydroxybutyl acrylate, acryloylmorpholine, acrylamide, isostearyl acrylate, and isododecyl acrylate.
3. The method for preparing the enhanced OCA optical adhesive according to claim 1, characterized in that: The crosslinking agent is a multifunctional acrylate, including one or more of trimethylolpropane tri(meth)acrylate, tripentaerythritol octaacrylate, ethoxylated trimethylolpropane triacrylate, pentaerythritol tetraacrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate, and trimethylolpropane tris(3-mercaptopropionic acid) ester; the solvent includes tetrahydrofuran.
4. The method for preparing the enhanced OCA optical adhesive according to claim 1, characterized in that: The initiator includes one or more of hydrogen peroxide, dimethyl azobisisobutyrate, azobisisobutyronitrile, azobisisovaleronitrile, azobiscyclohexylcarbonitrile, 2,2'-azobis(N-butyl 2-methylpropionamide), 1,2-bis(2,4,4-trimethyl-2-pentyl)diazene, and 2,2'-azo-bis-(2,4-dimethyl-4-methoxyvaleronitrile).
5. The method for preparing the enhanced OCA optical adhesive according to claim 1, characterized in that: The free radical scavenger includes one or more of 2,2,6,6-tetramethyl-1-(undecyoxy)-4-piperidinol carbonate, 1,2,3,4-butanetetracarboxylic acid and 2,2-bis(hydroxymethyl)-1,3-propanediol and 3-hydroxy-2,2-dimethylpropanal, a polymer of 1,2,2,6,6-pentamethyl-4-piperidinyl ester, tetramethylpiperidin oxide, phenothiazine, and 2,6-di-tert-butyl-4-methylphenol.
6. The method for preparing the enhanced OCA optical adhesive according to claim 1, characterized in that: The preparation method of the modifier comprises: The modifier monomers A and B are mixed in a mass ratio of 0.5 to 2:1 and added into tetrahydrofuran, stirred to remove oxygen, and reacted at 50 to 70° C. for 5 to 10 hours to obtain a modifier; Wherein, the modifier monomer A includes one or more of hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, and hydroxybutyl (meth)acrylate; the modifier monomer B includes one or more of N-hydroxymethyl acrylamide, isophorone diisocyanate, or hydrogenated dicyclohexylmethane diisocyanate.
7. The method for preparing the enhanced OCA optical adhesive according to claim 1, characterized in that: The reaction, wherein the reaction temperature is 50-80° C., and the reaction time is 4-24 hours.
8. The method for preparing the enhanced OCA optical adhesive according to claim 1, characterized in that: The baking process comprises the following steps: the baking temperature is 60 to 100° C., the baking time is 3 to 10 minutes, and the heating rate is 3 to 8° C. / min.
9. An enhanced OCA optical adhesive prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the enhanced OCA optical adhesive as claimed in claim 9 in display screen manufacturing.